2010
DOI: 10.1098/rspa.2010.0095
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic object recognition using pressure sensing

Abstract: Hydrodynamic sensing is instrumental to fish and some amphibians. It also represents, for underwater vehicles, an alternative way of sensing the fluid environment when visual and acoustic sensing are limited. To assess the effectiveness of hydrodynamic sensing and gain insight into its capabilities and limitations, we investigated the forward and inverse problem of detection and identification, using the hydrodynamic pressure in the neighbourhood, of a stationary obstacle described using a general shape repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…As seen in the parameterization by Bouffanais et al [6], the shape of a cylinder can be easily expressed as a series of perturbations of increasing complexity based on a conformal map. As the complexity increases, the order of the pole needed to represent the perturbation in potential flow also increases, resulting in a faster decay of the pressure generated by the perturbation.…”
Section: Strategy and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in the parameterization by Bouffanais et al [6], the shape of a cylinder can be easily expressed as a series of perturbations of increasing complexity based on a conformal map. As the complexity increases, the order of the pole needed to represent the perturbation in potential flow also increases, resulting in a faster decay of the pressure generated by the perturbation.…”
Section: Strategy and Motivationmentioning
confidence: 99%
“…Larger fish, potentially predatory, are not well modeled by small oscillatory dipoles and instead would be better approximated by blunt moving objects. Experiments by Vogel and Bleckmann [80] Two studies ( [70] and [6]) have considered parameterizations of the shape of an arbitrary object suitable for modeling flow and pressure distributions in potential flow. The authors have used these parameterizations to demonstrate how a simulated fish swimming in a potential flow could identify the shape of an object by swimming past or around it.…”
Section: Introductionmentioning
confidence: 99%
“…shown that a body moving in prescribed motion around another body can use distributed measurements over some time to create a complete map of the flow, provided the two bodies are in relatively close proximity, of the order of one body length or less (Sichert, Bamler & van Hemmen 2009;Bouffanais, Weymouth & Yue 2010); the presence of an external flow makes identification easier. Bouffanais, Weymouth & Yue (2010) analyzed the mapping of the environment via pressure signals in two ways, first to determine the pressure signal of a given obstacle shape and then to find the location and shape of a body given its pressure signal.…”
Section: Flow Reconstruction: Inviscid Theory For Two-dimensional Inmentioning
confidence: 99%
“…Bouffanais, Weymouth & Yue (2010) analyzed the mapping of the environment via pressure signals in two ways, first to determine the pressure signal of a given obstacle shape and then to find the location and shape of a body given its pressure signal. They found that insufficient information is provided about the shape by a pressure signal at a single location.…”
Section: Flow Reconstruction: Inviscid Theory For Two-dimensional Inmentioning
confidence: 99%
“…The sensing of the turbulent wake behind a cylinder using a virtual sensor has been described previously by Akanyeti et al [10], and object identification using pressure sensors has been completed for static arrays [11][12][13]. Further wake navigation algorithms have been previously developed based on the predicted pressure signal [14]. Research by Venturelli et al [15] sampled a KVS using two symmetric linear lateral lines running on either side of a three-dimensional 'boat-shaped' craft, as an analogue of the posterior lateral line.…”
Section: Introductionmentioning
confidence: 99%